Deaf students in the classroom, inclusive bilingual education: systematic review - de la Paz Elez, Pedro; Rodríguez Martín, Vicenta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This qualitative research carries out a systematic review to find out what are the factors that hinder and favor the learning process of bilingual deaf students in primary school. This work follows the guidelines of the PRISMA statement. The databases consulted have been Web of Science, Scopus, ERIC and Google Scholar, reviewing a total of 190 empirical studies, in Spanish and English, between the years 1997 and 2021. The results obtained show that there are few publications in this regard and there is evidence the need to publicize the situation of this group in order to continue advancing and educating.